Kewenangan Intelijen Kejaksaan dalam Sistem Ketatanegaraan Indonesia: Analisis Yuridis terhadap Batas Kewenangan dan Kepastian Hukum - Dhotun Kendaru Rahmando; Sherlock H. Lekipiouw; Hendrik Salmon (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the authority of prosecutorial intelligence within the Indonesian constitutional system following Law Number 11 of 2021. The main issue lies in normative ambiguity and overlapping authority with other institutions, affecting legal certainty. The findings show that prosecutorial intelligence authority is a legally attributed power but lacks clear limitations in scope, procedures, and oversight. This condition potentially leads to conflicts of authority and abuse of power. Therefore, harmonization of laws and strengthening of oversight mechanisms are necessary to ensure legal certainty and the effectiveness of the criminal justice system.